Field reports form for submitting seasonal observations of Iowa birds, Eloise Armstrong and Eugene Armstrong, spring 1992 - Armstrong, Eloiseet al; Armstrong, Eugeneet al (1992)
List of birds and locations contributed by Eloise Armstrong and Eugene Armstrong with observers Jim Sinclair, Dennis Thompson, Reid I. Allen, Pam Allen and others. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of spring 1992. Plustek - flatbed